Kesantunan Berbahasa dalam Kasus Ferdy Sambo pada Acara Rosi di Kompas TV - Mufida Maryamah Gustia; Yetty Morelent; Marsis Marsis; Syofiani Syofiani; Ineng Naini (Fakultas Sastra Universitas Ekasakti, 2023)
The purpose of research on language politeness in the case of Ferdy Sambo on the Rosi program on Kompas TV is to describe the language politeness practiced by Rosi Silalahi and Patra M Zen in the ROSI talk show. The data collection was obtained by using the observing technique and followed by the note taking technique. The researcher found obedience and violation of politeness maxims. The obedience maxim of politeness is found in the maxim of tact, the maxim of generosity, the maxim of humility, the maxim of conformity, the maxim of sympathy, and the maxim of praise. While violations of the principle of politeness were found, violating the maxim of tact, the maxim of generosity, the maxim of humility, the maxim of praise and no violations of the maxim of compatibility and sympathy were found.